2004
DOI: 10.1521/pedi.18.2.151.32776
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics of Partner Violent Men: A Q-Sort Approach

Abstract: Our objective was to develop a personality profile of men who are violent toward their partners. A total of 52 experienced clinicians described either a current male patient who was violent toward his partner (and only toward his partner) or who was maritally distressed but nonviolent using the Shedler-Westen Assessment Procedure-200 (SWAP-200), a Q-sort instrument designed to harness the judgments of clinicians. Partner-violent patients showed significantly higher scores on the SWAP-200 antisocial and borderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 23 publications
4
35
0
Order By: Relevance
“…Of these, 14-19% had been diagnosed with one of the following disorders: paranoid personality disorder, antisocial personality disorder, obsessive-compulsive personality disorder and avoidant personality disorder [7] . In addition, a cross-sectional study found that the presence of personality disorders in a partner was associated with maintenance of psychopathology in the partner diagnosed with BPD [78] .…”
Section: Characteristics Of the Partners Of People With Borderline Pementioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 14-19% had been diagnosed with one of the following disorders: paranoid personality disorder, antisocial personality disorder, obsessive-compulsive personality disorder and avoidant personality disorder [7] . In addition, a cross-sectional study found that the presence of personality disorders in a partner was associated with maintenance of psychopathology in the partner diagnosed with BPD [78] .…”
Section: Characteristics Of the Partners Of People With Borderline Pementioning
confidence: 99%
“…With regard to predictors, the presence of anxious attachment was partly accounted for by the severity of symptoms in the partner with BPD [77] . Another cross-sectional study found that the presence of anxious attachment in partners demonstrated their desire to prevent severe reactions from the partner with BPD (e.g., threats of a break-up, suicide attempts, substance abuse relapse) [78] .…”
Section: Characteristics Of the Partners Of People With Borderline Pementioning
confidence: 99%
“…These findings could aid clinicians working with forensic populations in terms of guiding and supporting their clinical decisions about management and treatment. Until now the SWAP-200 had been used only with less severe forensic populations (Porcerelli et al, 2004); however, the results of this study confirm the absence of a ceiling effect for Antisocial PD, suggesting that this scale has the capacity to measure severe forms of the disorder.…”
Section: Validity Of the Severity Cut-off Score In The Antisocial Pd mentioning
confidence: 49%
“…Although the SWAP-200's validity with PD forensic patients has been supported by its developers and by independent researchers, the clinical populations in these studies appear to be at the less severe end of personality pathology and criminality (Bradley, Hilsenroth, Guarnaccia, & Westen, 2007;Fowler & Westen, 2010;Porcerelli, Cogan, & Hibbard, 2004). The preliminary results of a small sample study (n = 30) of forensic PD patients detained in high security conducted by the current authors were promising in terms of the SWAP-200 offering a more parsimonious classification of DSM PD categories compared with the SCID-II and improving the convergent validity of the PD categories when both SWAP-200 and SCID-II were assessed against other instruments assessing interpersonal functioning and attachment (Marin-Avellan, McGauley, Campbell, & Fonagy, 2005).…”
mentioning
confidence: 99%
“…Many have witnessed family violence or were victims of abuse as children (Delsol & Margolin, 2004;Gortner, Gollan, & Jacobson, 1997) and often present personality pathologies (notably, borderline, narcissistic, and antisocial; e.g. Fowler & Westen, 2011;HoltzworthMunroe & Stuart, 1994;Jackson, Sippel, Mota, Whalen, Schumacher, 2015;Mauricio, Tein, & Lopez, 2007;Porcerelli, Cogan, & Hibbard, 2004;Saunders, 1992) and substance abuse problems (e.g., Kraanen, Vedel, Scholing, Emmelkamp, 2014;Singh, Tolman, Walton, Chermack, Cunningham, 2014). Despite the frequent co-occurrence of the perpetrator's own trauma history, personality disorders, and substance abuse, it is important to note that incorporation of more structured and specific intervention strategies of these aspects is not typically targeted into IPV current treatments, limiting their effectiveness.…”
Section: Interventions For Perpetratorsmentioning
confidence: 99%